2014
DOI: 10.1371/journal.pone.0097749
|View full text |Cite
|
Sign up to set email alerts
|

Rac1-Dependent Lamellipodial Motility in Prostate Cancer PC-3 Cells Revealed by Optogenetic Control of Rac1 Activity

Abstract: The lamellipodium, an essential structure for cell migration, plays an important role in the invasion and metastasis of cancer cells. Although Rac1 recognized as a key player in the formation of lamellipodia, the molecular mechanisms underlying lamellipodial motility are not fully understood. Optogenetic technology enabled us to spatiotemporally control the activity of photoactivatable Rac1 (PA-Rac1) in living cells. Using this system, we revealed the role of phosphatidylinositol 3-kinase (PI3K) in Rac1-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…Studies have shown that the overexpression of Rac1 in tissue samples from patients with prostate cancer is associated with poor patient prognosis 32 . Studies have also shown that activation of Rac1 via the PI3K/AKT pathway is essential for the induction of migration in PC3 cells 33 . It has also been observed that inhibition of active form of Rac1 (GTP bound Rac1) causes antimigratory effects in prostate cancer cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the overexpression of Rac1 in tissue samples from patients with prostate cancer is associated with poor patient prognosis 32 . Studies have also shown that activation of Rac1 via the PI3K/AKT pathway is essential for the induction of migration in PC3 cells 33 . It has also been observed that inhibition of active form of Rac1 (GTP bound Rac1) causes antimigratory effects in prostate cancer cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Rac1 occurs in several different types of tumors including breast (16,17), colon (18), bladder (19), and gastric cancer (20,21). Rac1 overexpression was observed in metastatic gastric (21), breast (15), prostate (22), bladder upper urinary tract cancer (19). Rac1 promoted prostate cancer progression and recurrence upon activation by VAV3, a GEF for Rac1 activation (14).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, I predict that the effect of fibrinogen on WAVE complex‐1 formation is abolished in the absence of SYK–PI3K interaction and the WAVE complex‐1 does not form in the absence of this interaction, which is in agreement with Kato et al . and Weering et al . , who show that inhibiting PI3K inhibits lamellipodia extension.…”
Section: Discussionmentioning
confidence: 88%